Airtightness impact on energy needs and airflow pattern: a numerical evaluation for mechanically ventilated dwellings in France. Issue 2 (2nd April 2016) - Richieri, F.; Moujalled, B.; Salem, T.; Carrié, F.R.
ABSTRACT: This paper aims to assess the impact of the envelope airtightness on both heating needs and airflow patterns for the case of a single-detached dwelling as function of the ventilation system. An original numerical approach based on the energy simulation tool TRNSYS coupled to the multi-zone airflow and contaminant transport model COMIS was used to compare the performance of four mechanical ventilation strategies. The impacts of the envelope leakage location (facades and/or ceiling), the zone configuration (one- or multi-zone model), the climatic and wind exposure conditions (exposed or surrounded by obstructions) were also investigated. The results show a significant increase of the heating needs when the air permeability at 4 Pa is increased depending on the climatic conditions. Furthermore, the desired airflow pattern, and hence the dispersion of pollutants from main rooms to service rooms can be significantly disturbed especially in the case of humidity-sensitive ventilation system.